Pengaruh Desentralisasi, Partisipasi Anggaran, Komitmen Organisasi, dan Motivasi Kerja Terhadap Kinerja Manajerial SKPD Kabupaten Karanganyar - Suprianto, Agus, Dr. Zulfikar, SE, M.Si (2016)
This study aims to obtain empirical evidence in analyzing the influence of decentralization, participation budgeting, organizational commitment, and motivation to work on managerial performance SKPD . Research use survey method with questionnaires as an instrument of primary data collection. The study population was a manager or employee of the local Secretariat (SETDA). The sample used was the Head of Division and Chief of the Division employees Karanganyar regency Regional Secretariat (SETDA). Samples were taken using a convenience sampling technique, based on predefined criteria obtained 40 respondents. Model analysis used is multiple linear regression with Windows SPSS version 15.0. The results showed that decentralization, participation budgets, organizational commitment, and motivation positive effect on managerial performance. The magnitude of the effect (R2) Decentralization, Participation Budget, commitmen Organization and Work Motivation of the effectiveness of managerial performance area is 62.1%. While the remaining 37.9% is influenced by other independent variables that are not observed in this study.